Pengaruh Latihan Sepakbola Empat Gawang Terhadap Keterampilan Passing Dan Dribbling - Rizky Pratama; Wilda Welis; Hadi Pery Fajri; Hanif Badri (JURUSAN KESEHATAN DAN REKREASI FAKULTAS ILMU KEOLAHRAGAAN, 2022)
The problem of this research is the player's ability to do poor passing and dribbling. Lack of variety of forms of football game practice. The purpose of this research is to find out the Influence of Four-Goal Football Practice.On Passing and Dribbling Skills at Fc Marunggi United Pariaman City. This type of research is pseudo-experimental research. The research was conducted on 19 March - 22 Agustus 2021 at Fc Marunggi United football club in Pariaman city. The population of Fc Marunggi United football club consists of 24 players. As for the way in determining samples, researchers use purposive sampling methods. The samples in this study were as many as 20 players. Based on the analysis of data in this study using t-test. The results of the data processing in this study were thitung on passing skills (10,78) > ttabel (2,093) and thitung on dribbling skills (10,64) > ttabel (2,093) after being treated. It means there is a significant influence on the four-goal football training form on the passing and dribbling skills of fc Marunggi United Kota Pariaman.